Strata titles in west Malaysia / Norazlan Ahmad - Ahmad, Norazlan (Faculty of Law, 1986)
The period after the World War II witnessed the increasing demand for urban housing in most countries,and Malaysia was no except ion to it. The period after the World War II witnessed theincreasing demand for urban housing in most countries,and Malaysia was no except ion to it. In relation with the increasing significance of these buildings, it carried altogether with the demand for ownership rights over them. As the Malays ian I s land administrat ion is based upon the Australian's Torrens system,where legal ownership is dependent on the registration of titles to land, the issuing of a document evidencing title to the land is of much important. In case where a house which had been built on land,there was no difficulties to issue a document of title tothe said land.